Jászi-dilemmák: Egy fejezet a szociológia magyarországi intézményesülésének történetéből - Huszár, Tibor (Szociológiai Szemle, 2024)
Oscar Jászi stands in the centre of this study on the institutionalization of Hungarian sociology at the beginning of this century. He was a productive writer and a gifted organizer who effectively promoted the publication of the first sociological periodical in Hungary. His attempts to secure an academic appointment failed. His study trip to France contributed to his realization of how the impossibility to separate science and politics hindered progress in sociology. His voluminous 1912 study on ethnic relations in Hungary clearly indicates the dilemmas of a sociology that simultaneously pursues political objectives.